The relationship between firms' free cash flow and investment: an empirical study on Malaysian public listed companies - Wera, Lukam (Universiti Malaysia Sarawak, (UNIMAS), 2011)
This study examines the relationship between firms' investment, as dependent variable, and the respective free cash flow, as the independent variable. The study on the relationship has also been extended further to include other independent variables such as firms' debt ratio, size (a measure of the total asset value), dividend payout, agency problem, Tobin's Q (a measure of the share market value) and cash account uses. The sample used comprises of 110 non-financial companies listed on the Bursa MalaYSia) It was found that there is a significantly negative relationship between firms' investment and the respective free cash flow. Also, higher partially significant relationship has been found between firms' investment and dividend payout and debt ratio negatively and positively with Tobin's Q. While lower partially significant relationship was found between firms' investment and frrms' size and cash account uses negatively and positively with agency problem.